2018
DOI: 10.4062/biomolther.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Donepezil, an Acetylcholinesterase Inhibitor, on Impaired Learning and Memory in Rodents

Abstract: A previous study in humans demonstrated the sustained inhibitory effects of donepezil on acetylcholinesterase (AChE) activity; however, the effective concentration of donepezil in humans and animals is unclear. This study aimed to characterize the effective concentration of donepezil on AChE inhibition and impaired learning and memory in rodents. A pharmacokinetic study of donepezil showed a mean peak plasma concentration of donepezil after oral treatment (3 and 10 mg/kg) of approximately 1.2 ± 0.4 h and 1.4 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
(36 reference statements)
2
35
0
Order By: Relevance
“…Furthermore, since donepezil exposure decreased AChE levels in zebrafish brain (Figure 2), these findings parallel rodent and human data on donepezil-evoked changes in brain AChE activity (Ben-Azu et al, 2019; Kasa et al, 2000; Shin et al, 2018), and corroborate the proposed link between cholinergic signaling and stress responses (Janowsky and Risch, 1984). However, the dose-dependent aspect of such effects on zebrafish behavior, cortisol, and AChE activity merit further consideration, since behavior and cortisol showed a clear dose-dependent curve here, whereas the AChE activity did not (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, since donepezil exposure decreased AChE levels in zebrafish brain (Figure 2), these findings parallel rodent and human data on donepezil-evoked changes in brain AChE activity (Ben-Azu et al, 2019; Kasa et al, 2000; Shin et al, 2018), and corroborate the proposed link between cholinergic signaling and stress responses (Janowsky and Risch, 1984). However, the dose-dependent aspect of such effects on zebrafish behavior, cortisol, and AChE activity merit further consideration, since behavior and cortisol showed a clear dose-dependent curve here, whereas the AChE activity did not (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, zebrafish exposure to physostigmine and scopolamine (a muscarinic receptor antagonist) concomitantly suppresses these anxiolytic effects (Cho et al, 2012). Because donepezil has long been associated with modulating the nicotinic acetylcholine receptors (Shin et al, 2018), this mechanism may underlie its distinct anxiety effects (Figures 1 and 2) from those of physostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…Group 3 received donepezil (an inhibitor of acetylcholinesterase) at a daily oral dose by gavage of 10 mg/kg body weight (b.w.) ( Shin et al, 2018 ) with daily dose of AlCl 3 (70 mg/kg, ip). Groups 4 to 7 received a daily oral dose of extracts (cladodes, fruit peel, fruit pulp and polysaccharide) (100 mg/kg b.w.)…”
Section: Methodsmentioning
confidence: 99%
“…In the past few decades, it has been observed that drugs such as donepezil [4] and Huperzine A [5] could alleviate distinct symptoms associated with AD. However, there are still no drugs that can retard the progression of AD.…”
Section: Introductionmentioning
confidence: 99%